Clinical and microbiological profile of enteric fever in a tertiary care hospital - Dr. Kavitha Balasubramanian; Dr. Madhusudhan NS; Dr. Malini A.; Dr. Johnson C. (Tropical Journal of Pathology and Microbiology, 2019)
Background: Enteric fever is largely prevalent in India. This study is done to know the clinical profile of typhoid & paratyphoid fever and to study the pattern of antimicrobial susceptibility among Salmonella species. Materials and Methods: This observational hospital based prospective study was conducted from August 2015 to December 2016 in patients admitted in medicine department of a tertiary hospital. The clinically suspected cases were diagnosed by blood culture, stool culture, Widal test and Typhoid test. The antimicrobial susceptibility pattern of Salmonella species was isolated. Results: 121 cases of clinically suspected entericfever were found to be either blood culture positive or serology positive for enteric fever. The mean age of the participants was 30.55±12.65 years with 76 (62.81%) males and 45 (37.19%) females. The most common symptom were fever, headache and chills. Other findings were bradycardia 67(55%), abdominal tenderness 25 (21%), splenomegaly 32 (26%) and hepatomegaly 14 (11.5%). Blood culture was done in 80 patients, 6 were growing S. typhi; 28 were growing S. paratyphi. Out of 107 cases Widal was done, 42 Widal positive for typhoid fever; 37 was paratyphoid positive, 28 Widal negative. Out of 121 cases, 53 were paratyphoid, 58 were typhoid fever, 10 were diagnosed based on clinical criteria of enteric fever. All the isolates were sensitive to ceftriaxone. Conclusion: This study points to a higher yield of enteric fever by blood culture, also the no of paratyphoid cases is relatively higher as compared to typhoid cases.